Problems encountered from the use (or misuse) of Rayleigh damping. - Hall, John F. (Earthquake engineering & structural dynamics.)
Rayleigh damping is commonly used to provide a source of energy dissipation in analyses of structures responding to dynamic loads such as earthquake ground motions. In a finite element model, the Rayleigh damping matrix consists of a mass-proportional part and a stiffness-proportional part; the latter typically uses the initial linear stiffness matrix of the structure. Under certain conditions, for example, a non-linear analysis with softening non-linearity, the damping forces generated by such a matrix can become unrealistically large compared to the restoring forces, resulting in an analysis being unconservative. Potential problems are demonstrated in this paper through a series of examples. A remedy to these problems is proposed in which bounds are imposed on the damping forces.